Eye tracking study on air traffic controller trigger event analysis - Soong, Vincent (2019)
With the advancements of technology and safety standards in the aviation industry, air travel has proved to be a popular mode of transport around the world. The increase of commercial flights had been prevalent for the past few decades, and it has been forecasted to grow at a faster rate in the future. The increase of air traffic has a direct implication on air traffic controllers as they face the challenge of managing airspace with tighter separation levels and more complicated air routes. The onus is on the aviation industry to uphold high industry performance levels and safety standards by improving air traffic management tactics and solutions. The study of eye movement has been common in recent years, and it was used to show a correlation between visual perception and cognitive thinking. Coupled with the improvements in the technology of eye tracking devices, it has also proven to be a reliable method of measurement for studying mental, cognitive workload and human performance. Hence, eye tracking has been used in a wide variety of fields to investigate information processing by studying the eye fixations of the test subject. There had been past research relating eye movements and air traffic control, but there has not been extensive coverage of study how different situational events in an air traffic scenario can affect the eye data from the air traffic controllers. Therefore, this project aims to research and study on how different situational events in an air traffic control scenario can affect the eye tracking patterns of the air traffic controller. By studying the eye monitoring data during these events, this project aims to develop a model to differentiate expertise levels of the air traffic controllers. Through the findings of this study, it was found that there could be a significant difference between the eye monitoring data of the different expertise levels of air traffic controllers during trigger events.